Lifetime measurements of the D+, D0, Ds+, and Λc+ charmed particles - Alvarez,MP; Barate,R; Bloch,D; Bonamy,P; Borgeaud,P; Burchell,M; Burmeister,H; Brunet,JM; Calvino,F; Cattaneo,M; Crespo,JM; d'Almagne,B; et al. (Zeitschrift Fur Physik C Particles and Fields, 1990)
Using a high-statistics sample of more than 1000 reconstructed charmed-particle decays, the lifetimes of the weakly decaying charmed mesons and of the Λc+ baryon have been measured: Mathematical expression © 1990 Springer-Verlag.